Antioxidant Species in Grapes and Wines via Spectrophotometric Methods: No Quenching Effects by Copper(II) and Yeast Derivative Treatments. (13th March 2019) - Tamasi, Gabriella; Pardini, Alessio; Bonechi, Claudia; Donati, Alessandro; Leone, Gemma; Consumi, Marco; Pagni, Daniele; Cini, Renzo; Rossi, Claudio; Magnani, Agnese
Abstract : Analytical determinations for selected parameters in grapes/wines help planning technology treatments in the vineyards and cellars, improving the quality of final products and preserving consumers' health. The study first reports a comparative analysis for selected parameters on juice, must, and wines at alcoholic and malolactic fermentation stages, from 2013 harvest and refined bottled wines from 2010–2012 and 2015 vintages. This was considered preliminary to the main goal of the work that consisted of testing if the contents of certain antioxidant principles were influenced or not by additions of copper(II) and/or selected fermentation yeasts. Particular attention was devoted to antioxidant molecule contents: total polyphenols, anthocyanins, trans -resveratrol, and quercetin. Selected samples were then analyzed in absence and in presence excess Cu(II)-sulfate (5 mgCu/L) and/or yeast derivatives to evaluate possible effects on antioxidant concentrations. The total polyphenols contents in untreated wine samples were as high as 3334 ± 60 mg (gallic acid)/L and averaged 2883 ± 299 mg/L (wines 2010–2013 and 2015). In particular, high contents of quercetin and quercetin glucoside were found in Sangiovese/Canaiolo/Colorino (harvest 2015) wine, being 21 ± 2 and 3.0 ± 0.2 mg/L, respectively. Even resveratrol had high concentrations in 100% Sangiovese wine (1.3 ± 0.1 mg/L, harvest 2015; 2.6 ± 0.3 mg/L, harvest 2010). Interestingly, no significant effect was revealed by Cu(II) and/or yeast derivatives on antioxidant contents for wine matrixes. In fact, determinations (validated through the standard addition methods) of trans -resveratrol for untreated Sangiovese wines (1.18 ± 0.09 mg/L) and for wines treated with excess Cu(II) and excess Cu(II) plus excess yeasts mixtures (1.24 ± 0.09 mg/L and 1.22 ± 0.05 mg/L) did not differ significantly.